Autismo e educação musical: uma proposta de formação de professores - Pendeza, Daniele Pincolini (2018)
The literature has highlighted the lack of knowledge of music educators about the redflags for autism, fact that draws attention, taking account their core role as teachers in a main stage for the identification of this disorder. Considering the absence of subjects that contemplate autism in undergraduate courses, the musical educator is unprepared to recognize these early signs of this disorder in their teaching practice. The present study had as main objective to verify the effectiveness of a teacher training proposal for the identification of autism redflags with students of the UFSM Music Licensing course. Through a mixed approach, using a single group experimental design, the training with 20 hours was performed to 12 students graduating in music. Content theories on child development was included, linking developmental psychology and pragmatic, for contextualization and identification of the redflags for autism. The effectiveness of the training was evaluated by measures of knowledge evaluation, in the pre- and post-test phases and in each class, through the observation and identification of the behaviors of redflags for autism in videos of children with typical development and autism in the context of the classroom. The results show, in a preliminary way, their effectiveness, since it amplified the knowledge of the future musical educators about the typical development and redflags for autism, generating, even, a significant social impact on the participants of the research, who were able to change their prejudices about autism and inclusion. However, we suggest the development of the training with a larger number of participants and the evaluation of the videos by qualified judges, to confirm their effectiveness in the field of education.